Software defined networking (SDN) and its security issues - Abdul Aziz, Normaziah; Mantoro, Teddy; Khairudin, M. Aiman; A. Murshid, A. Faiz (Institute of Electrical and Electronics Engineers Inc., 2019)
The demand of network infrastructure and services is ever increasing. The network architecture and related technology must be flexible enough to accommodate the ever-growing number of users. Software-Defined Networking (SDN) is an approach of networking architecture that improvise conventional network in terms of scalability, security, and availability. At the same time, SDN is vulnerable to security threats as well. This paper studies on SDN architecture, the improvement of SDN from conventional network, the vulnerability and threats in SDN, and possible solutions to some security threats examples. It gives an overview of SDN and security – the architecture advantages that can be leveraged to secure network systems, and the security threats that may occur if improper design and deployment of SDN take place.